Pola Konsumsi dan Persepsi Generasi Z terhadap Ketahanan Pangan: Pengembangan Consumer-Centric Framework - Satato, Yuniarto R; Prabowo, Bayu Ade; Pramudya, Aditya Linggar (Forum Kerjasama Pendidikan Tinggi, 2025)
Generation Z as digital natives have unique food consumption patterns that potentially influence national food security. This study aims to analyze Generation Z's consumption patterns and perceptions of food security and develop a conceptual framework to optimize their participation. Using a mixed method approach, the research was conducted on 150 STIEPARI Semarang students through online surveys, digital food diaries (30 respondents), Focus Group Discussions (32 participants), and in-depth interviews (10 informants). Data were analyzed using descriptive-inferential statistics and thematic content analysis with phenomenological approach. Results show 73.3% of respondents prefer practical food with fast food consumption frequency of 4.2 times per week and 45.7% make purchases through online platforms. Despite limited conceptual understanding of food security (70% of informants), Generation Z demonstrates high environmental awareness (78.7%) and optimism towards technological solutions (89.2%). Structural Equation Modeling identifies social media influence as the dominant factor (β = 0.387) affecting consumption behavior. The developed Consumer-Centric Food Security Framework for Generation Z integrates four dimensions: Digital Influence, Sustainability Consciousness, Convenience Orientation, and Technology Optimism. This framework provides strategic guidance to optimize Generation Z's role in food security through digital approaches and technology-based programs.